Problems of German and European Eastern policy (Czech Journal of International Relations, 2024)
Kurt Biedenkopf:born 1930, graduate of political science at Davidson College in the USA. In 1955 he completed his law studies in Frankfurt and in 1960 he received a Master of Law degree from Georgetown University in Washington. In the years 1967-1969 he was rector of the Ruhr-Universität in Bochum. In 1973, he became the director of the Düsseldorf concern Henkel. In 1965 he joined the CDU, in 1973 he was elected CDU general secretary. In 1989, he actively participated in the changes in the former GDR. In 1990 he was elected Prime Minister of Saxony.